Evolution of the Modern Sports Fan: Communicative Approaches - Billings, Andrew C.; Brown, Kenon A. (Lexington Books, 2017)
The concept of “fandom” has been revolutionized over the past 20 years because of various technological, cultural, and communicative advancements. Evolution of the Modern Sports Fan: Communicative Approaches explores the elements of the sports fan that have markedly changed since the turn of the century. Inherent within these investigations is the role of communication in a multitude of forms (mediated, relational, etc.) as the prototypical sports fan has most heavily shifted within this domain. From the advent of social media to the rise of fantasy sport to the increased media platforms in which to consume sport, the sports fan has never had more options for consumption—and for the rendering of his/her opinions. This edited volume offers an opportunity to advance what we now know about American sports fandom as well as the ability to debunk what scholars thought they knew about sports fandom that has now shifted.